Pemberdayaan UMKM Pedesaan melalui Literasi dan Promosi Digital di Desa Partoruan Lumban Lobu - Muhammad Nabil Alfikri (Getpress Management Journals, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, particularly in rural areas that serve as the foundation of community-based economic activities. However, the limited utilization of digital technology remains a major challenge in expanding market reach and improving the competitiveness of local products. This study aims to analyze the effectiveness of digital promotion strategies in enhancing the capacity of MSMEs in Partoruan Lumban Lobu Village. A descriptive qualitative method was employed through observation, interviews, and documentation involving 15 local MSME actors. The findings reveal that digital marketing training provided to the community has contributed to an increase in sales performance, demonstrating greater understanding and application of digital marketing practices. These results indicate that the implementation of digital promotion strategies can significantly improve the visibility and income of MSMEs. Therefore, sustainable collaboration between village authorities, academic institutions, and digital communities is recommended to strengthen the rural digital economic ecosystem.